2020
DOI: 10.7150/thno.42153
|View full text |Cite
|
Sign up to set email alerts
|

Human urine-derived stem cells protect against renal ischemia/reperfusion injury in a rat model via exosomal miR-146a-5p which targets IRAK1

Abstract: Rationale: Ischemia/reperfusion injury (IRI) is a major cause of acute kidney injury (AKI) that is associated with high morbidity and mortality, and for which specific treatments are lacking. In this study, we investigated the protective effect of human urine-derived stem cells (USCs) and their exosomes against IRI-induced AKI to explore the potential of these cells as a new therapeutic strategy. Methods: USCs were derived from fresh human urine. Cell surface marker expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 64 publications
2
94
0
Order By: Relevance
“…Regarding T cells, we found that USC–derived EVs suppressed T cell proliferation under stimulatory conditions, in line with the previously reported immunosuppressive capacity of USCs and MSCs on T cells [ 34 , 66 , 67 ]. This effect has been extensively studied in MSCs and has been associated with the secretion of immunosuppressive cytokines [ 68 , 69 ] and miRNA, in particular miRNA146–5p, which was enriched in USC’s EVs, as reported previously [ 70 , 71 ]. However, further studies are warranted for full characterization of the effects of USC–derived EVs on T cells to address, for example, the EVs uptake, a more comprehensive study of the T cell activation, and the molecules responsible for their observed immune suppressive effects on these cells.…”
Section: Discussionmentioning
confidence: 64%
“…Regarding T cells, we found that USC–derived EVs suppressed T cell proliferation under stimulatory conditions, in line with the previously reported immunosuppressive capacity of USCs and MSCs on T cells [ 34 , 66 , 67 ]. This effect has been extensively studied in MSCs and has been associated with the secretion of immunosuppressive cytokines [ 68 , 69 ] and miRNA, in particular miRNA146–5p, which was enriched in USC’s EVs, as reported previously [ 70 , 71 ]. However, further studies are warranted for full characterization of the effects of USC–derived EVs on T cells to address, for example, the EVs uptake, a more comprehensive study of the T cell activation, and the molecules responsible for their observed immune suppressive effects on these cells.…”
Section: Discussionmentioning
confidence: 64%
“…They play crucial negative regulatory roles in inducing the degradation or translational repression of protein-coding mRNAs 66 , 67 . Increasing evidence has shown that miRNAs play important roles in regulating macrophage-mediated inflammatory responses, including macrophage activation and polarization, tissue infiltration, resolution of inflammation, and kidney injury 68 - 70 . Researchers have revealed that miR-142 regulates profibrogenic macrophage gene expression in chronic inflammation 71 .…”
Section: Discussionmentioning
confidence: 99%
“…AKI is increasing in incidence and can be caused by trauma, sepsis, surgery, or nephrotoxic drugs, and ischemia-reperfusion injury (IRI) is one of its leading causes 2 . IRI disrupts the cellular redox balance and triggers excessive ROS production in the kidneys upon reperfusion, leading to a series of events that follow IRI-induced AKI (IRI-AKI) and include mitochondrial damage, energy depletion, tubular apoptosis and necrosis 3 - 5 . Moreover, incomplete recovery from AKI can trigger renal fibrosis and thus increase the risk of chronic kidney disease (CKD) and end-stage renal failure (ESRD) 6 - 8 .…”
Section: Introductionmentioning
confidence: 99%